The Influence Of Service Quality And Trust On Customer Satisfaction In The Use Of Bri Mobile (Brimo) In Arga Makmur City Of North Bengkulu - Abdul Haris Sahaq; Neri Susanti; Nenden Restu Hidayah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this study is to determine the extent to which service quality and trust influence customer satisfaction in using BRI Mobile (BRImo). This research is a qualitative descriptive research that is quantified. The method used is a questionnaire. The sample of this research is 85 respondents. The results showed that multiple linear regression obtained Y=27.918+0.251(X1)+0.186(X2)+4.174, meaning that there is a positive or unidirectional relationship between Service Quality (X1) and Trust (X2) on customer satisfaction in using BRI Mobile (BRImo). The results of the service quality test (X1) show t count 3.438>t table 1.989 and significance 0.000 <0.05, then the results of the hypothesis Ha are accepted and Ho are rejected, meaning that service quality has a positive and significant effect on customer satisfaction in using BRI Mobile. The results of the Trust test (X2) show t count 2.896>t table 1.989 and significance 0.000<0.05, then the results of the hypothesis Ha are accepted and Ho are rejected, meaning that Trust has a positive and significant effect on customer satisfaction in using BRI Mobile. Furthermore, the result of the f table value is 9.190>2.71, it is concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between service quality (X1) and Trust (X2) on customer satisfaction variable (Y) in the use of BRI Mobile in Arga Makmur city. This can be seen at the significance level of 0.000 <0.05